Periodontal soft tissue increase induced by periodontally accelerated osteogenic orthodontics surgery - Ye Han; Lili Miao; Jian Liu; Xiao Xu; Zhaoguo Yue; Min Xu; Chang Shu; Li Xu; Jianxia Hou (BMC, 2022)
Abstract Objectives To quantitatively assess periodontal soft tissue changes, including gingival thickness and keratinized gingiva width after periodontally accelerated osteogenic orthodontics (PAOO) surgery by digital measurements.  Methods This study enrolled 15 maxillaries with 89 anterior teeth and 16 mandibles with 94 anterior teeth from Chinese adult patients with skeletal Angle Class III malocclusion for whom PAOO surgery was proposed during orthodontic treatment. Intraoral scanning and cone beam computed tomography (CBCT) examinations were performed before PAOO surgery and 6 months after the surgery. Keratinized gingiva width was measured on the digital model acquired by intraoral scanning. The gingival thickness was measured using a digital three-dimensional (3D) model based on the combination of digital intraoral scanning and CBCT data. Results The mean gingival thickness before surgery was 0.91 ± 0.32 mm and 1.21 ± 0.38 mm at 6-month after PAOO. Patients showed periodontal soft tissue increase with a mean gingival tissue gain of 0.30 ± 0.33 mm. At 1 mm, 2 and 3 mm apical to cemento-enamel junction (CEJ) levels, the gingival thickness increase of the mandible was higher than that of the maxilla (0.38 ± 0.30 mm vs. 0.24 ± 0.31 mm, 0.43 ± 0.35 mm vs. 0.26 ± 0.41 mm, 0.36 ± 0.27 vs. 0.25 ± 0.32 mm, respectively, all P < 0.05). Moreover, the sites of gingival thickness ≤ 1 mm before surgery showed more tissue gain than the sites > 1 mm (0.36 ± 0.32 mm vs. 0.18 ± 0.31 mm, P < 0.001). The mean keratinized gingiva width at T0 was 3.88 ± 1.22 mm, and increased 1.05 ± 1.24 mm 6 months after PAOO surgery. Moreover, a digital 3D model for gingival thickness measurement based on the combination of digital intraoral scanning and CBCT displayed high reliability and accuracy with an intra-class correlation coefficient (ICC) of 0.897. Conclusion PAOO could improve an insufficient quantity of periodontal soft and hard tissues in patients with skeletal Angle Class III malocclusion, including the gingival thickness and keratinized gingiva width. A digital 3D model based on the combination of digital intraoral scanning and CBCT data could provide a new digital measurement of gingival thickness with high accuracy and reliability.